Proposed Improvement Strategy for Gold Installment Product of Bank Syariah Mandiri (Case Study at Sub Branch XYZ) - Indrayani, Yeni Puspa; Aliludin, Arson (The Indonesian Journal of Business Administration, 2015)
Abstract. Bank Syariah Mandiri (BSM), the largest Islamic bank in Indonesia, has launched Gold Installment Product in March 2013. This product is included in the category of consumer financing with murabahah (sale and purchase) scheme. Gold Installment is a complementary financing gold-based products previously owned by BSM namely Gold Pawn.Internal data shows portfolio of Gold Installment in BSM Sub Branch XYZ is still considered very low. In the year of 2013, it accounted IDR100,905,706.77 of the total financing portfolios of IDR91,072,965,069.37. Meanwhile, in 2014 it amounted to IDR802,547,002.95 of the total financing portfolios of IDR43,735,597,055.89. This final project is intended to conduct an analysis of Gold Installment Product as new financial products in general and its connection with the Gold Installment financing portfolio in Sub Branch XYZ Gold which is still very low.In the meantime, external analysis using PEST, Porter's Five Forces, and Customer Survey has been carried out. Furthermore, internal analysis using financial analysis, analysis of marketing, analysis of human resources, analysis of risk, SWOT analysis, product analysis, and analysis of performance. The analysis concludes that the root causes of the issue related to low achievement of Gold Installment are product feature that is not in accordance with public expectation which is still too expensive, quantity and quality of human resources, as well as insufficient promotion.As the recommendation business level and functional level strategy has been identified. In business level, BSM should re-identify the strategy and deliver Cost Leadership Strategy as the business level strategy of Gold Installment. Meanwhile, for functional level, several activities should be carried out include product improvement, price adjustment, promotion program improvement, after sales service program, and human resource development. Furthermore, Improvement strategies for financing products Gold Installment done in two stages which are the improvement in Sub Branch XYZ is internal improvement and external improvement in general in BSM with proposals related to the product owner is Pawning Division (PWD).Keyword : Islamic Banking, Financing, Murabahah, Gold InstallmentÂ